Pengaruh Kegiatan Menggambar Imajinatif Terhadap Kecerdasan Visual Spasial Anak Usia 5-6 Tahun di RA Khairin Islamic School (KIS) Kecamatan Medan Tembung Tahun Pelajaran 2019/2020 - muhammad azis (Jurnal CARE (Children Advisory Research and Education), 2020)
The purpose of this study is 1) to find out the spatial visual intelligence of children aged 5-6 years in the class who are doing imitating drawing activities. 2) to find out the spatial visual intelligence of children aged 5-6 years in the class carrying out imaginative drawing activities. 3) to determine the effect of imaginative drawing activities on the spatial visual intelligence of children aged 5-6 years at RA Khairin Islamic School (KIS), Medan Tembung Subdistrict T.A. 2019/2020. This research is a quantitative research with experimental research type. The population in this study were all students aged 5-6 years at RA Khairin Islamic School (KIS) Medan Tembung, with a total population of 32 students divided into 2 classes. Data collection instruments using observation, documentation studies, and analysis techniques using normality tests, homogeneity tests and hypothesis testing. Based on the research conducted, it can be concluded that 1) The results of the control class research by using imitating drawing activities amounted to 15 people, having an average value of pre-test (5,667) and post-test (7,553). 2) The results of the experimental class research using imaginative drawing activities totaling 17 people, have an average value of pre-test (5,412) and post-test (9,647). 3) there is a significant influence between imaginative drawing activities on early childhood spatial visual intelligence on the home-specific theme environment in the Medina class at RA Khairin Islamic School (KIS) Medan Tembung T.A. 2019/2020. This can be seen from the average value of children's spatial visual intelligence after being given treatment is 5.412 to 9.657. This is also evidenced from the results of hypothesis testing which is.